China's enterprise reform : changing state/society relations after Mao - You, Ji, 1955- (Routledge, 1998)
The author demonstrates how China's post-Mao reforms have produced a quiet revolution from below as the process of political and economic liberalization has accelerated.
Keywords: China -- Economic conditions -- 1976-2000.; China -- Economic policy -- 1976-2000.; China -- Politics and government -- 1976-; Chine -- Conditions économiques -- 1976-2000.; Chine -- Politique économique -- 1976-2000.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Economic history; Economic policy; Politics and government; China; Since 1976